A Retrospective Review of a Bed-mounted Projection System for Managing Pediatric Preoperative Anxiety - Caruso, Thomas J. (Pediatr Qual Saf, 2018)
INTRODUCTION: Most children undergoing anesthesia experience significant preoperative anxiety. We developed a bedside entertainment and relaxation theater (BERT) as an alternative to midazolam for appropriate patients undergoing anesthesia. The primary aim of this study was to determine if BERT was as effective as midazolam in producing cooperative patients at anesthesia induction. Secondary aims reviewed patient emotion and timeliness of BERT utilization. METHODS: We conducted a retrospective cohort study of pediatric patients undergoing anesthesia at Lucile Packard Children’s Hospital Stanford between February 1, 2016, and October 1, 2016. Logistic regression compared induction cooperation between groups. Multinomial logistic regression compared patients’ emotion at induction. Ordinary least squares regression compared preoperative time. RESULTS: Of the 686 eligible patients, 163 were in the BERT group and 150 in the midazolam. Ninety-three percentage of study patients (290/313) were cooperative at induction, and the BERT group were less likely to be cooperative (P = 0.04). The BERT group was more likely to be “playful” compared with “sedated” (P < 0.001). There was a reduction of 14.7 minutes in preoperative patient readiness associated with BERT (P = 0.001). CONCLUSIONS: Although most patients were cooperative for induction in both groups, the midazolam group was more cooperative. The BERT reduced the preinduction time and was associated with an increase in patients feeling “playful.”